Effect of ethanol-wet-bonding technique on resin-enamel bonds - Muhammet Kerim Ayar; Cemal Yesilyurt; Cemile Kedici Alp; Tahsin Yildirim (Elsevier, 2014)
Background/purpose: It was reported that more stable resin--dentin bonds were achieved by using ethanol-wet bonding. Because it would be difficult to saturate acid-etched dentin with ethanol without saturation enamel, the study was conducted to evaluate the microtensile bond strength (μTBS) of adhesive resins bonded to enamel using water- and ethanol-wet-bonding techniques. Materials and methods: Flat enamel surfaces from extracted bovine incisor teeth were conditioned with 37% H3PO4 (for 15 seconds) before bonding. Two commercial adhesives (Single Bond 2 and All Bond 3) were applied to enamel using water- and ethanol-wet-bonding techniques (for 1 minute) as follows: group I, Single Bond 2 and water-wet bonding; group II, All Bond 3 and water-wet bonding; group III, Single Bond 2 and ethanol-wet-bonding; and group IV, All Bond 3 and ethanol-wet-bonding. Resin-bonded teeth were stored in distilled water (for 24 hours) and sectioned in beams for μTBS testing. μTBS results were analyzed by a two-way ANOVA and LSD test. The resin-enamel interfaces were examined by SEM. Results: The following mean μTBS values were obtained: 17.4 MPa for group I, 26.4 MPa for group II, 28.7 MPa for group III, and 31 MPa for group IV. For both adhesives, the obtained adhesive-enamel μTBS values with the ethanol-wet-bonding technique were significantly higher than those of the water-wet-bonding technique (P < 0.05). Conclusion: The ethanol-wet-bonding technique may increase the bond strength of commercial adhesives to enamel. The chemical composition of the adhesives can affect the bond strength of adhesives when bonding to acid-etched enamel, using the ethanol-wet-bonding technique. Some adhesive systems used in the present study may simultaneously be applied to enamel and dentin using ethanol-wet-bonding. Furthermore, deploying ethanol-wet-bonding for the tested commercial adhesives to enamel can increase the adhesion abilities of these adhesives to enamel.